Penerapan Model Mastery Learning Dalam Meningkatkan Pemahaman Matematik Siswa - Hismi Hadria Setiawati; Agus Hikmat Syaf (Al-Aulad: Journal of Islamic Primary Education, 2018)
This purpose of this research is to know the implementation of the Mastery Learning to improve the ability of mathematic in every cycles, and rising of activities in learning process through Mastery Learning. The methodolgy in this research is Classroom Action Research (CAR) which consists of two cycles, whereby in each cycle consists of planning, action, observation, and reflection. Subject of this research is students of class IV (grade four) MIN 1 Bandung, West Java Indonesia. The results in this research is the implementation of Mastery Learning in each cycles by teachers and students increased sharply. In addition, the average mathematical ability of students in the first cycle which is 79.75, and in the second cycle is 83.85, furthermore the rate of mathematical ability in the last cycle is 86,7 (a very large majority). Thus, the application of Mastery Learning can improve students' mathematical ability.